2004
DOI: 10.3102/00028312041002365
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Teacher Interventions to Student Needs During Cooperative Learning: How to Improve Student Problem Solving and Time On-Task

Abstract: This study tested a model of teacher interventions (TIs) conducted during cooperative learning to examine how they affected students' subsequent time on-task (TOT) and problem solving. TIs involved groups of ninthS uppose you are a teacher and have several groups of students working on an algebra problem. Some groups are working productively, while others are not. When do you intervene? How should you intervene? What kinds of interventions are likely to improve students' problem solving?In the present study, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
1
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(85 citation statements)
references
References 26 publications
5
75
1
4
Order By: Relevance
“…This may explain the negative effect of social activities on group performance. Furthermore, in many studies the activities we consider to be social activities are considered to be off-task activities which are usually considered to be deleterious for learning and perfomance (Chiu 2004;Klein and Schnackenberg 2000).…”
Section: Group Performancementioning
confidence: 99%
“…This may explain the negative effect of social activities on group performance. Furthermore, in many studies the activities we consider to be social activities are considered to be off-task activities which are usually considered to be deleterious for learning and perfomance (Chiu 2004;Klein and Schnackenberg 2000).…”
Section: Group Performancementioning
confidence: 99%
“…Hardly any empirical research exists on whether and how contingent support affects task effort. The only study that we encountered was the study of Chiu (2004) in which a positive relation was found between support in which the teacher first evaluated students' understanding (assuming that this promoted contingency) and student's task effort.…”
Section: Scaffolding Task Effort and Appreciation Of Supportmentioning
confidence: 99%
“…Diagnosing or evaluating students' understanding enables contingency and this is effective. Chiu (2004) for example found that when supporting small groups with the subject-matter, evaluating students' understanding before giving support was the key factor in how effective the support was. Although evaluation is not necessarily the same as contingency, it most probably facilitates contingency.…”
Section: Scaffolding Task Effort and Appreciation Of Supportmentioning
confidence: 99%
“…There are also studies that have coded teachers' and pupils' discourse into a variety of categories to compare different learning situations and to assess the effects of teachers' interventions on pupils' behaviour (e.g., Hertz-Lazarowitz and Shachar, 1990;Chiu, 2004;Dekker and ElshoutMohr, 2004;Gillies, 2004;Ding et al, 2007;Webb et al, 2009). For example, Hertz-Lazarowitz and Shachar (1990, p. 83) identify four types of practices -"(1) teacher praises and encourages pupils in relation to task performance; (2) teacher interacts with pupils in an intimate-egalitarian orientation; (3) teacher stages herself as a central figure in the classroom; (4) teacher interacts with pupils in a rigid authoritarian orientation" -and found that teachers' verbal behaviour differed significantly between traditional whole class instruction and interactions in group work.…”
Section: Introductionmentioning
confidence: 99%